Cisplatin, the Timeless Molecule - Annaluisa Mariconda; Jessica Ceramella; Alessia Catalano; Carmela Saturnino; Maria Stefania Sinicropi; Pasquale Longo (Inorganics, 2025)
Cisplatin was the first metal-based anticancer drug introduced into clinical use. It is a “small” molecule, but it represented a very “big” discovery. Since it was introduced on the market, it has not been withdrawn, despite being not free of side effects, owing to its peculiarity of being highly effective in the treatment of cancer. Anticancer activity of the platinum-based complexes was discovered with this molecule; since then, several other platinum-based drugs have been developed and tested in preclinical studies against cancer cells; however, only a few of them reached clinical trials, and their side effects are not much less than cisplatin. Despite the constraints of drug resistance and side effects, chemotherapy remains a fundamental strategy in cancer treatment. Nowadays, cisplatin remains one of the most-used anticancer agents in treating lung, colon, ovary, testicles, bladder, cervix, and many more cancers, although cisplatin resistance represents a major hurdle in cancer treatment. Will there ever be another drug that can overcome the side effects of cisplatin but at the same time be able to block tumors as does cisplatin?